Mobilization of gold into lake sediments. - Schmitt, Harold Rolf. (University of Ottawa (Canada), 1993)
Geochemical exploration methods are able to contribute significantly to the detection of concealed Au mineralization in glaciated terrains. Gold analyses of lake sediments from the glaciated Canadian Shield have been used since the mid-1980s to explore for Au mineralization. For lake sediments to be an effective indicator of Au mineralization, the element must migrate in solution or adsorbed on suspensates in the boreal forest zone where low relief and disorganized drainage restricts dispersal and concentration in clastic form. Organic-rich profundal lake sediments often contain anomalous Au contents near Au mineralization, suggesting that Au is entering the lake environment in mobile form. Confirmation of the processes by which Au is mobilized into lake sediments could thus contribute to improved exploration methodologies. This study investigated the nature of Au mobility and dispersion into lake sediments under alkaline and acid hydrological conditions in the southern Canadian Shield. The study makes recommendations for exploration strategies to be employed under these conditions. Three field areas were selected for detailed study: Napier Lake, Ontario; PAP Lake, Saskatchewan; and Foster Lake, Manitoba. (Abstract shortened by UMI.)
Keywords: Hydrology.